2007
DOI: 10.1016/j.cardiores.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with ω-3 PUFA increases adiponectin and attenuates ventricular remodeling and dysfunction with pressure overload

Abstract: Dietary supplementation with omega-3 PUFA attenuated pressure overload-induced LV dysfunction, which was associated with elevated plasma adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 34 publications
(51 reference statements)
3
88
1
4
Order By: Relevance
“…This resulted in attenuation of left ventricular remodeling and dysfunction. 85,117,118 In a subsequent study, a linoleateenriched high-fat diet (but not saturated high-fat diet) attenuated cardiac hypertrophy, left ventricular chamber dilation, and improved systolic function in aged hypertensive heart failure rats. 119 Moreover, a high-fat diet reduced cardiac hypertrophy and improved contractile function in Dahl salt-sensitive rats.…”
Section: Approaches To Treat Left Heart Failure Inhibiting Fat Oxidationmentioning
confidence: 94%
“…This resulted in attenuation of left ventricular remodeling and dysfunction. 85,117,118 In a subsequent study, a linoleateenriched high-fat diet (but not saturated high-fat diet) attenuated cardiac hypertrophy, left ventricular chamber dilation, and improved systolic function in aged hypertensive heart failure rats. 119 Moreover, a high-fat diet reduced cardiac hypertrophy and improved contractile function in Dahl salt-sensitive rats.…”
Section: Approaches To Treat Left Heart Failure Inhibiting Fat Oxidationmentioning
confidence: 94%
“…fluence cardiac remodeling [11,12]. Low levels of adiponectin are associated with a further progression of left ventricular hypertrophy in patients presenting with hypertension, left ventricular diastolic dysfunction, and hypertrophy [13].…”
mentioning
confidence: 99%
“…Because acromegaly is also a systemic disorder characterized by morbidities similar to those of a metabolic syndrome, hypoadiponectinemia may be involved in the pathogenesis of insulin resistance and related metabolic disorders as well as cardiac changes present in active acromegaly [10][11][12][13][14][15][16][17]. Indeed, adiponectin levels in acromegalic patients have been reported variably as higher than [18] or similar to [19,20] those in normal controls.…”
mentioning
confidence: 99%
“…They established that dietary fish oil reversed the inhibitory effects of a long-term sucroserich diet on serum leptin and total adiponectin levels [53] . Since then, many studies have confirmed that dietary fish oils and omega-3 fatty acids increase total adiponectin concentrations [54,56,[105][106][107][108] . Sneddon and colleagues examined the effects of CLA and omega-3 fatty acids on plasma leptin and adiponectin concentrations [55] .…”
Section: Adiponectinmentioning
confidence: 97%